Predictive control of a multi-drive solar pumping system - Riedemann, Javier; Jara, Werner; Pena, Ruben; Andrade Aguero, Ivan Eric; Blasco-Gimenez, Ramon; Melin, Pedro (My University, 2019)
In this paper, a multiple drives solar-pumping system is presented. The system is based on a single-stage photovoltaic (PV) topology where an array of solar panels is connected to multiple inverters supplying equal centrifugal pumps. The inverters are operated to extract the maximum power from the PV system and a predictive control strategy for the machines currents is proposed. The performance of the system is verified via simulations.
Keywords: adjustable speed drive; control of drive; electrical drive; multi-machine system